Data Security in Internet of Things in Future 5G Networks - Rohini S Hanchate, Dr.R.A.Karthika (International Journal of Advanced Science and Technology, 2020)
In the era of technology Internet of things comprises of worldwide heterogeneous interconnected devices to share the information in order to achieve more automated things. These things can be sensors actuators, software, hardware and network connectives. IOT is growing rapidly therefore, Internet of Things desires to be built in such a way to avoid hazard to their security and privacy. Though new world of smart devices will make human life easier with rapidly growing technologies, Internet of Things desires to be built to avoid hazard to their security and privacy. In the IOT, to communicate with smart things all objects associated to the comprehensive Internet which leads to new challenges in security and privacy where huge data sensed and exchanged by smart objects, to prevent unauthorized identification objects i.e., confidentiality, authenticity, and integrity In this context, the more independent and intelligent systems get, problems like the authentication and privacy of Objects emerge, and accountability of things in their acting will have to be considered. Prior to Transfer the data to objects or things, the procedure of encryption along with secret key is applied on data to generate cipher text and later user reproduces the original data by applying decryption by using identical private key which may share 2 by different objects. The principle method of model of the IoT Security is reliant upon secrecy, data integrity and accessibility. With regards to IoT, secrecy provides solution for securing protection of IoT gadgets; data integrity takes care of the information contained inside the gadget and confirms the original data at destination side without altering it in the communication link while accessibility deals with availability of the gadget with access control mechanism which most recent issue in security.